2019
DOI: 10.3389/fcell.2019.00060
|View full text |Cite
|
Sign up to set email alerts
|

Cancer-Associated Fibroblasts Build and Secure the Tumor Microenvironment

Abstract: Tumor cells reside in a highly complex and heterogeneous tumor microenvironment (TME), which is composed of a myriad of genetically stable non-cancer cells, including fibroblasts, immune cells, endothelial cells, and epithelial cells, and a tumor-specific extracellular matrix (ECM). Cancer-associated fibroblasts (CAFs), as an abundant and active stromal cell population in the TME, function as the signaling center and remodeling machine to aid the creation of a desmoplastic tumor niche. Although there is no den… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
349
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 361 publications
(356 citation statements)
references
References 157 publications
6
349
0
1
Order By: Relevance
“…Cancer-associated fibroblasts (CAFs) in the immediate vicinity of cancer cells play an important role in tumorigenesis in various physicochemical ways by reducing apoptosis and improving the proliferation, migration and viability of cancer cells [58,59]. CAFs residing in TME are heterogeneous cells with different origins, different functions (pro or anti-tumor activities) and different surface markers such as alpha-smooth muscle actin (α-SMA), myosin light chain 9 (MYL9), myosin light chain kinase (MYLK), matrix metalloproteinase 2 (MMP2), decorin (DCN) and collagen type I alpha 2 (COL1A2) [60][61][62][63].…”
Section: Cancer-associated Fibroblast (Cafs)mentioning
confidence: 99%
See 1 more Smart Citation
“…Cancer-associated fibroblasts (CAFs) in the immediate vicinity of cancer cells play an important role in tumorigenesis in various physicochemical ways by reducing apoptosis and improving the proliferation, migration and viability of cancer cells [58,59]. CAFs residing in TME are heterogeneous cells with different origins, different functions (pro or anti-tumor activities) and different surface markers such as alpha-smooth muscle actin (α-SMA), myosin light chain 9 (MYL9), myosin light chain kinase (MYLK), matrix metalloproteinase 2 (MMP2), decorin (DCN) and collagen type I alpha 2 (COL1A2) [60][61][62][63].…”
Section: Cancer-associated Fibroblast (Cafs)mentioning
confidence: 99%
“…It is a complex network composed of fibrous proteins (collagen, elastin), glycosaminoglycans (hyaluronic acid), proteoglycans (chondroitin sulfate, heparan sulfate), and glycoproteins (fibronectin 1 (FN1), laminins, tenascin C (TNC)) [115,116]. ECM proteins can be produced by many stromal cell types and tumor cells, however, CAFs are the main source for synthesis, secretion, assembly, and modification of the ECM composition and organization [60,117].…”
Section: Ecmmentioning
confidence: 99%
“…These include targeting the ECM remodeling enzymes such as the lysyl oxidase family and MMPs, or targeting CAF-derived molecular signals (e.g. CXCR4, TGF-B, HGF) (reviewed in 9 ).…”
Section: Discussionmentioning
confidence: 99%
“…We have previously reported that activated cancer-associated fibroblasts (CAFs) influence outcome in EAC and the biological properties of esophageal CAFs that promote tumor progression 8, 9 . CAFs have also been shown to influence the immune cell infiltrate and response to chemotherapy in a range of tumors 10-12 .…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have also illustrated the correlation between CAF and ECM in the regulation of the metastatic niche and chemoresistance [134]. Cancer associated fibroblasts broadly infiltrate tumor stroma, comprising two different cellular populations (PMID: 15549095), namely cells ancillary to ephitelium and cells with myofibroblastic differentiation, whose phenotype is characterized by alpha-SMA expression and exert a direct modulation to cancer proliferative potential, tumoral angiogenesis and disseminative potential and aggressiveness, in both solid [135,136] and hematological malignancies [137,138].…”
Section: Integrins and Tumorigenesismentioning
confidence: 99%